Knowledge and attitudes about Human Papilloma Virus (HPV) vaccination and cervical cancer screening among women in rural Uganda - Innocent H, Nkonwa; D’onofrio, Michael J.; Ngonzi, Joseph; Wilson, Muhhwezi; Banula, Cecil; Bunjo, Kiku Tony; Mirembe, Florence (Journal of Health, Medicine and Nursing, 2016)
Abstract Cervical cancer is one of the major causes of death among women worldwide. There is an established linkage between cervical cancer and Oncogenic Human Papilloma virus (HPV) strains 16 and 18. While cervical cancer is widely understood as a fatal disease, knowledge and awareness of cervical cancer and HPV in Uganda has been limited even among health workers. Objectives: To establish the level of knowledge in regard to HPV vaccination among parents/guardians of the vaccinated girls and to assess the attitudes to HPV vaccination among parents/guardians of the vaccinated girls. Methods: A cross-sectional study where 384 mothers/ female guardians of vaccinated girls were recruited into the study. One hundred and sixty four women reported knowing about HPV i.e. 42.7% out of the 384 women. The variables which were significantly associated with knowledge of HPV among the women were; age below 30years, higher education level with P<0.001, Marital status with P<0.001, tribe P=0.021, Religion, P=0.001 and occupation with P <.001. Conclusion: The level of knowledge of HPV among the women of Nakasongola district was relatively low. High education among the mothers contributed to better knowledge. The general attitude towards HPV vaccination was positive among mothers though there is still need for the populations to appreciate HPV and cervical cancer in general.
Keywords: Human Papilloma Virus (HPV); cervical cancer screening; women; Uganda